Pptc7 is an essential phosphatase for promoting mammalian mitochondrial metabolism and biogenesis - Natalie M. Niemi; Gary M. Wilson; Katherine A. Overmyer; F.‐Nora Vögtle; Lisa Myketin; Danielle C. Lohman; Kathryn L. Schueler; Alan Attie; Chris Meisinger; Joshua J. Coon; David J. Pagliarini (2019)
Mitochondrial proteins are replete with phosphorylation, yet its functional relevance remains largely unclear. The presence of multiple resident mitochondrial phosphatases, however, suggests that protein dephosphorylation may be broadly important for calibrating mitochondrial activities. To explore this, we deleted the poorly characterized matrix phosphatase Pptc7 from mice using CRISPR-Cas9 technology. Strikingly, Pptc7